Enhancing Teaching Quality of Teachers through Open Broadcaster Software - Anni Holila Pulungan; Rika Rika; Khairunnisa Batubara (BIRCU, 2023)
The transition of learning system from offline to online due to Covid-19 caused the teachers at MIS Ar Rasyid feel surprised and felt they must be able to use online media for their teaching learning process. This activity aims to improve the competence and professionalism of teachers at Madrasah Ibtidaiyah Ar Rasyid jalan Besar Tadukan Raga, STM Hilir-Deli Serdang in using Open Broadcaster Software. There are 10 teachers involved in this activity. This program is carried out through lectures, workshops, question and answer methods, and demonstrations. The lecture method is used to describe the basic concepts of OBS, demonstrations are carried out for direct practice of using it followed by the discussions about problems in the OBS steps, workshops are held to train and assist teachers. They design learning videos based on one basic competency. The results achieved from this activity are that the teachers are very enthusiastic, respond so positively and are very motivated to make learning videos through OBS. Teachers are also increasingly competent and professional in teaching using OBS to support the success of their classroom interaction.